Validation of Instruments for Measuring Affective Outcomes in Gifted Education. Issue 4 (November 2020) - Callahan, Carolyn M.; Azano, Amy Price; Park, Sunhee; Brodersen, Annalissa V.; Caughey, Melanie; Bass, Erika L.; Amspaugh, Christina M.
With increasing attention to examining cognitive strengths and achievements related to social and emotional variables, it is imperative that instruments developed and used to assess change be valid and reliable for measuring underlying constructs. This study examines instruments identified and/or developed to measure four noncognitive constructs (i.e., student engagement, self-efficacy, growth mindset, and stereotype threat) as outcome variables in a study with elementary-aged students in high-poverty rural communities. The process of creating and examining the psychometric properties of these instruments is a necessary step in documenting the usefulness of the instruments not just in our study but also in other studies with elementary students. We note in our descriptions of the development and assessment of measures that underlying factors may or may not parallel those identified in the general population or in older students and that measurement of noncognitive variables in the population of young gifted students requires considerable attention.